2018
DOI: 10.1111/bpa.12641
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the heterogeneity of MS lesions using positron emission tomography: a reappraisal of their contribution to disability

Abstract: The biological mechanisms driving disability worsening in multiple sclerosis (MS) are only partly understood. Monitoring changes in lesion load on MRI has a limited predictive value on the progression of clinical disability, and there is an essential need for novel imaging markers specific for the main candidate mechanisms underlying neurodegeneration which include failing myelin repair, innate immune cell activation and gray matter neuronal damage. Positron Emission Tomography (PET) is an imaging technology b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 98 publications
(119 reference statements)
0
15
0
1
Order By: Relevance
“…From the imaging perspective, standard MRI measures (such as T2-weighted and gadolinium-enhanced T1-weighted sequences) correlate only modestly with disability and lack the ability to differentiate between pathological correlates of MS: namely inflammation, oedema, axonal loss, demyelination, remyelination and gliosis [131]. As a result, advanced MRI techniques including myelin water fraction (MWF) [132,133], diffusion tensor imaging (DTI) [134,135] and magnetisation transfer ratio (MTR) [136,137], as well as positron emission tomography (PET) [43,138], have been variably used to measure myelin dynamics.…”
Section: Neuroimagingmentioning
confidence: 99%
“…From the imaging perspective, standard MRI measures (such as T2-weighted and gadolinium-enhanced T1-weighted sequences) correlate only modestly with disability and lack the ability to differentiate between pathological correlates of MS: namely inflammation, oedema, axonal loss, demyelination, remyelination and gliosis [131]. As a result, advanced MRI techniques including myelin water fraction (MWF) [132,133], diffusion tensor imaging (DTI) [134,135] and magnetisation transfer ratio (MTR) [136,137], as well as positron emission tomography (PET) [43,138], have been variably used to measure myelin dynamics.…”
Section: Neuroimagingmentioning
confidence: 99%
“…70 A large proportion of lesions considered inactive on MRI were very active on PET, indicating subacute or chronic active lesions. 66 The number of these active lesions was correlated with individual disability trajectories, suggesting that they may be major players in MS progression. 66 TSPO PET also revealed a diffuse brain inflammatory component that is higher in PMS, predominates in areas close to the cerebrospinal fluid, and correlates with microstructural damage.…”
Section: Other Promising Biomarkersmentioning
confidence: 95%
“…66 The number of these active lesions was correlated with individual disability trajectories, suggesting that they may be major players in MS progression. 66 TSPO PET also revealed a diffuse brain inflammatory component that is higher in PMS, predominates in areas close to the cerebrospinal fluid, and correlates with microstructural damage. 69 Using myelin radiotracers, 65 it has been shown that MS patients have heterogeneous individual remyelination profiles, which are critical in determining disability accrual.…”
Section: Other Promising Biomarkersmentioning
confidence: 95%
See 1 more Smart Citation
“…A second key application of PET in MS research is the quantification of demyelination and remyelination, which is now possible using benzothiazole-and stilbene-derived radiotracers. 5 We now know that each patient with MS is characterized by a specific remyelination profile, which reflects the individual level of spontaneous myelin repair in response to a demyelinating insult and is critical to determine disease evolution and disability. 8 In the next future, the application of myelin-specific fluorinated compounds will allow a wider use of PET in the context of clinical trials evaluating the efficacy of drugs designed to promote myelin repair.…”
Section: B Bodini and B Stankoffmentioning
confidence: 99%